2020
DOI: 10.3389/fcell.2020.556162
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Targets G6PDH to Disrupt Redox Homeostasis and Inhibit Renal Cell Carcinoma Proliferation

Abstract: Glucose-6-phosphate dehydrogenase (G6PDH) is the rate-limiting enzyme in the pentose phosphate pathway (PPP) and plays a crucial role in the maintenance of redox homeostasis by producing nicotinamide adenine dinucleotide phosphate (NADPH), the major intracellular reductant. G6PDH has been shown to be a biomarker and potential therapeutic target for renal cell carcinoma (RCC). Here, we report a previously unknown biochemical mechanism through which caffeine, a well-known natural small molecule, regulates G6PDH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
(73 reference statements)
3
3
0
Order By: Relevance
“…In addition, it also increased the levels of pro-inflammatory cytokines such as TNF-α and IFN-γ. These results are in line with the previously known inhibitory effect of caffeine on the adenosine-A2a receptor pathway [ 62 ], which is one of the immunosuppressive pathways involved in cancer [ 63 , 64 ]. This capacity of caffeine to modulate the immune system in the tumor surroundings alters another important hallmark (i.e., the ability to avoid immune destruction).…”
Section: Benefits Of Caffeine On Healthsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, it also increased the levels of pro-inflammatory cytokines such as TNF-α and IFN-γ. These results are in line with the previously known inhibitory effect of caffeine on the adenosine-A2a receptor pathway [ 62 ], which is one of the immunosuppressive pathways involved in cancer [ 63 , 64 ]. This capacity of caffeine to modulate the immune system in the tumor surroundings alters another important hallmark (i.e., the ability to avoid immune destruction).…”
Section: Benefits Of Caffeine On Healthsupporting
confidence: 90%
“…Xu et al showed, through in silico studies, that caffeine is able to bind to glucose-6-phosphate dehydrogenase (G6PDH), which is considered a biomarker and potential therapeutic target for this type of cancer. Consistent with the above results, in this study, the use of caffeine at concentrations of up to 0.016 mM for in vitro studies and 60 and 120 mg/kg/day for in vivo studies decreased the viability and proliferation of ACHN and 786-O cancer cells both in vitro and in vivo [64]. G6PDH is an important target in cancer given that is normally upregulated in different cancers and its dysregulation can provide valuable conditions for cancer progression [66].…”
Section: Cancersupporting
confidence: 87%
“…However, the role of caffeine in the production of ROS is unclear. Xu et al (2020) observed that caffeine inhibits G6PDH activity, leading to a reduction in the intracellular levels of NADPH and ROS in renal carcinoma cells. Conversely, another previous study showed that the combination of caffeine and 5‐fluorouracil increased the levels of ROS, which was important to inhibit hepatocellular carcinoma cells (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine can also cause apoptosis via a variety of pathways, including those that are dependent on and independent of p-53, phosphatase and tensin homolog, PI3K/protein kinase B (AKT), and the mTOR pathway [95]. It is believed to have a therapeutic impact on renal cancer due to its ability to bind to glucose-6-phosphate dehydrogenase (G6PDH), considered a biomarker and possible therapeutic target for this kind of cancer, as shown in [83]. Research indicates that the use of coffee lowers biomarkers associated with inflammation, hence postponing weariness and enhancing endurance abilities.…”
Section: Long-term Studies On Studentsmentioning
confidence: 99%